2022
DOI: 10.37301/jmubh.v17i1.19983
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Budaya Organisasi, Kepemimpinan Dan Work Life Balance Terhadap Kinerja Pegawai Kantor Perwakilan Bank Indonesia Provinsi Riau

Abstract: This study aims to analyze the influence of organizational culture, leadership, and work life balance on employee performance at the Representative Office of Bank Indonesia, Riau Province. This research method is quantitative. The population in this study is the entire number of employees at the Representative Office of Bank Indonesia, Riau Province. The sampling technique in this research is using saturated sampling so that the number of samples is the same as the total population of 40 people. Analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
1
1
1
Order By: Relevance
“…Pacific Nusantara Bogor by 52.0%. This result is also in line with the research conducted by Irsyad et al (2022) which shows that there is an influence between leadership and employee performance where the better the leadership, the better the performance of employees at KPw BI Riau province.…”
Section: Jurnal Manajemen Universitas Bung Hattasupporting
confidence: 90%
“…Pacific Nusantara Bogor by 52.0%. This result is also in line with the research conducted by Irsyad et al (2022) which shows that there is an influence between leadership and employee performance where the better the leadership, the better the performance of employees at KPw BI Riau province.…”
Section: Jurnal Manajemen Universitas Bung Hattasupporting
confidence: 90%
“…The results of the study are those reported by Agustin et al (2022) reported that there was a positive and significant influence between organizational culture on employee performance as evidenced by the t-test of the organizational culture variable on the performance of 6.835 with a ttable of 2.026 because t-count > t-table and a significant level of 0.000 less than 0.05. The results of this study were not much different from those reported by Irsyad et al (2022) that there is an influence of organizational culture on performance with the value of sig. 0.049 <0.05 which indicates that the better the organizational culture, the better the performance of employees.…”
Section: Influence Of Organizational Culture To Performancecontrasting
confidence: 85%
“…Several researchers report that there is a positive and significant relationship between working from home simultaneously on employee performance (Soelistyoningrum, 2020;Sormin et al, 2021), and simultaneous organizational commitment to employee performance (Burhannudin et al, 2019;Agustin et al, 2022). Meanwhile, several research results report the simultaneous influence of organizational culture variables on employee performance (Girsang, 2019;Irsyad et al, 2022).…”
Section: Influence From Wfh Organizational and Organizational Culture...mentioning
confidence: 99%
“…Menurut (Fania et al, n.d.) keselarasan kehidupan kerja dapat dikatakan sebagai keselarasan individu dalam membagi fokus waktu bekerja maupun diluar kerja. Menurut (Irsyad et al, 2022) work life balance menjadi elemen yang berdampak kepada kinerja seorang pegawai. Keseimbangan kehidupan kerja yang tepat bisa mengurangi stres karyawan dan membuat mereka bahagia ditempat kerja ataupun dirumah.…”
Section: Work Life Balanceunclassified